2019
DOI: 10.1096/fj.201802237r
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐mediated proteasome targeting

Abstract: A majority of thousands of intracellular mammalian proteins are recognized by proteasome only being conjugated with ubiquitin (Ub), representing a universal degradation signal operated by the ubiquitination system. Ub‐independent proteasome targeting is rationalized by the existence of 2 types of direct proteasome signals (DPSs), specific amino acid sequences or post‐translational modifications, which are recognized by proteasome regulatory subunits. Historically, the first type was shown to exist in ornithine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 67 publications
1
33
0
1
Order By: Relevance
“…In vitro data support the notion that PA28αβ functions as a molecular sieve to regulate hydrophilicity of peptides generated by proteasomal cleavage in order to improve production of MHC I compatible antigenic peptides . A recent study suggests that PA28αβ proteasome complexes might degrade specific substrates that contain a novel charge-dependent degradation signal enriched in basic and flexible amino acids (Kudriaeva, Kuzina, Zubenko, Smirnov, & Belogurov, 2019). In cells, PA28αβ not only binds to the 20S particle but also to 26S proteasomes and possibly regulates the subcellular localization of 26S proteasome complexes (Cascio, Call, Petre, Walz, & Goldberg, 2002).…”
Section: Pa28alpha/betamentioning
confidence: 99%
“…In vitro data support the notion that PA28αβ functions as a molecular sieve to regulate hydrophilicity of peptides generated by proteasomal cleavage in order to improve production of MHC I compatible antigenic peptides . A recent study suggests that PA28αβ proteasome complexes might degrade specific substrates that contain a novel charge-dependent degradation signal enriched in basic and flexible amino acids (Kudriaeva, Kuzina, Zubenko, Smirnov, & Belogurov, 2019). In cells, PA28αβ not only binds to the 20S particle but also to 26S proteasomes and possibly regulates the subcellular localization of 26S proteasome complexes (Cascio, Call, Petre, Walz, & Goldberg, 2002).…”
Section: Pa28alpha/betamentioning
confidence: 99%
“…Recently, Kudriaeva and co-workers [9] characterized the myelin basic protein (MBP) DPS, showing that it is enriched in basic and flexible amino acids and its signaling function is charge-mediated. Notably, MBP mutants with negative or less positive surface charge showed a decrease in proteasomal degradation rate in vitro .…”
Section: Electrostatics: a Pivotal Player In Protein Structure And Inmentioning
confidence: 99%
“…The proteasome samples were prepared according to the protocol described in [33]. A bovine liver was mechanically homogenized in a hypotonic lysis buffer containing 10 mM Tris-HCl (pH 7.9), 1.5 mM MgCl 2 , 1 mM ATP, and 10 mM KCl.…”
Section: Purification Of Proteasomes From Bovine Livermentioning
confidence: 99%
“…Previously, it was shown that polyamines may increase the activity of enzymes, such as α-chymotrypsin [31], and act like chemical chaperones [32]. In contrast, proteins enriched with basic amino acids such as arginine and lysine may directly bind proteasomes [33,34] and are capable of further translocation into the proteolytic chamber [35,36]. Here, we investigate how the alkalization and increased concentration of polyamines may modulate the activity of proteasome, a part of the ubiquitin proteasome system (UPS), which specifically degrades thousands of intracellular proteins.…”
Section: Introductionmentioning
confidence: 99%